Infulance Street Lightning Taxes, Parking Taxes, and Hotel Taxes on Karawang Regency Local Revenue in 2009-2018 - Noviardy Nurkasyfi Sukma Purwawinata (INVENTORY: JURNAL AKUNTANSI, 2021)
The purpose of this research is: 1) to analyze the influence of the Street Lighting tax on the Local Revenue, 2) to analyze the influence of the Parking tax on the Local Revenue, 3) to analyze the influenceof the Hotel tax on the Local Revenue. The research object used in this study is the local revenue that derived from Street Lighting taxes,Parking taxes and Hotel taxes in 2009 – 2018. Based on the results of this study show that the Street Lighting tax has a positive and significant influence on local revenue in 2009 – 2018, this can be shown by the significant of the Street Lighting tax is 0,000 < 0,05. The analysis of this study indicates that Street Lighting taxes have an influence on local revenue. Parking tax Doesn’t Have any significant influence on local revenue in 2009 – 2018, this can be shown by the significant of the Parking tax is 0,212 >0,05. The analysis of this study indicates that Parking taxes Don’t have an influence on local revenue. Hotel tax has a positive and significant influence on local revenue in 2009 – 2018, this can beshown by the significant of the Hotel tax is 0,000 < 0,05. The analysis of this study indicates that Hotel taxes have an influence on local revenue.